Results of ocular hemodynamics in chronic ocular ischemic syndrome after bilateral carotid endarterectomy - (:unkn) unknown (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2009)
Background: The aim of this study was to investigate the effect of carotid endarterectomy on chronic ocular ischemic syndrome due to internal carotid artery stenosis progressed with transient ischemic attacks (TIAs). Methods: We examined 14 patients (12 males 2 females; mean age 62.3 +/- 5.4 years; range 47 to 71 years) with ocular ischemic syndrome due to bilateral internal carotid artery stenosis (>80% stenosis) who were treated by carotid endarterectomy. All patients had TIAs and complicated chronic ocular ischemic syndrome due to the ipsilateral internal carotid artery lesion. Preoperatively, dominant ocular sign was amaurosis fugax in II patients, quarantanopia in two, and blindness in one. Ophthalmic artery color Doppler flow imaging indicated ophthalmic artery flow direction and peak systolic flow velocity and was performed before and at 24 hours, one week, one month, and three months after surgery. Results:The ophthalmic artery flow directions were reversed in nine patients and antegrade in five patients preoperatively. In the six patients who experienced antegrade ophthalmic artery flow before carotid endarterectomy, the average peak systolic flow velocity was -0.029 +/- 0.05 m/s. Preoperative reversed flow resolved in each patient one week after surgery. All patients showed antegrade ophthalmic artery flow after surgery. The average peak systolic flow velocity in the patients, measured 24 hours after operation, when compared with preoperative antegrade flow values, rose significantly to 0.32 +/- 0.14 m/s (p<0.05). There was no significant difference when the first 24-hour-findings were compared with those observed one week, one month and three months after endarterectomy. During the follow-up period (mean, 18.5 months), no recurrent visual symptoms were observed. Conclusion: Carotid endarterectomy was effective for improving or preventing the progress of chronic ocular ischemia caused by internal carotid artery stenosis.
Keywords: Carotid endarterectomy; ocular ischemic syndrome; ophthalmic artery; transient ischemic attack; OCCLUSION